An investigation into the regulation of the topoisomerase IIα promoter in breast cancer cells exposed to doxorubicin : a thesis presented to Massey University in partial fulfillment of the requirement for the degree of Doctor of Philosophy in Biochemistry - Allen, Kirsty Ann (Massey University, 2003)
Chemotherapeutic drugs, such as doxorubicin, are some of the most effective agents for the treatment of breast cancer. Acquired resistance to these drugs often develops, however, and may preclude effective treatment. Such resistance is multifactorial in origin, but may include down-regulation of topoisomerase IIα (topo IIα) - an essential enzyme involved in normal DNA metabolism and a target for some of the anticancer drugs. A reduction in the levels of this enzyme is thought to reduce DNA damage induced by the drug-topo IIα complex and so increases the chances of survival. The mechanisms involved in this down-regulation and the development of resistance to doxorubicin are the focus of this study. Stable breast cancer cell lines, containing deletion constructs of the topo IIα promoter linked to the hGH reporter gene, were exposed to doxorubicin and both the reporter and endogenous gene expression were analysed in the surviving cells. It was shown that the reporter and endogenous topo IIα gene expression in the cell line containing the full length topo IIα promoter construct was no longer correlated in the surviving cells negating the use of this experimental system. Instead the endogenous expression of topo IIα and putative regulatory factors were investigated. Data suggest that specific cell lines show a down-regulation in the levels of the topo IIα protein. These changes were not due to changes in cellular proliferation rates, cell cycle profile or promoter sequence. Selected cell lines were analysed for changes in the relative amounts of specific transcription factors with putative roles in topo IIα gene regulation and for the expression of proteins proposed to have a role in the development of drug resistance. In specific cell lines, a reduction in topo IIα protein levels correlated with alterations in the relative amounts of NF-YA and/or Sp1. It was shown that the drug efflux pumps MDR1 and MRP1, as well as the heat shock factor Hsp70 were not involved in the survival of cells that were exposed to the drug. In vivo footprinting was attempted to detect changes in the in vivo binding of proteins to the topo IIα promoter after short term drug exposure.
Keywords: DNA topoisomerase II; Genetic regulation; Doxorubicin; Effect of drugs on cancer cells; Chemotherapy; Breast cancer; Fields of Research::250000 Chemical Sciences::250300 Organic Chemistry::250302 Biological and medical chemistry